Formation of nanostructured state in LaBGeO₅ monolithic glass using pulsed magnetic fields - Doroshkevich, A.S.; Shylo, A.V.; Volkova, G.K.; Glazunova, V.A.; Perekrestova, L.D.; Lyubchik, S.B.; Konstantinova, T.E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Using the methods of transmission electron microscopy, X-ray structure analysis and thermal differential analysis, it has been discovered that the pulsed magnetic field (PMF) intensifies homogeneous crystallization in LaBGeO₅-glass system, promotes homogenization of crystalline phase distribution inside the bulk of glass matrix. A possibility of obtaining the volume nanostructured state in LaBGeO₅-glass due to application of PMF has been suggested and experimentally grounded.